The Influence of Personality and Emotional Intelligence on Employee Performance is Moderated by Teamwork - Aulinah, Ina; Wahju, Wulandari; Mulyono, Mulyono (Clean and Sustainable Production, 2024)
The approach in this research takes the form of quantitative descriptive research. This research uses primart and secondary data. The sample numbered 56 using non probability sampling techniques. This study uses SEM-PLS. The results of this research show that: (1) personality has a positive and significant effect on employee performane. (2) emotional intelligence has a positive and significant effect on employee performance, (3) teamwork has a positive and significant effect on employee performance, (4) cooperation the team is unable to moderate the relationship between personality and employee performance, (5) teamwork is able to moderate the relationship between emotional intelligence and employee performance.